2016
DOI: 10.3762/bjoc.12.96
|View full text |Cite
|
Sign up to set email alerts
|

Marine-derived myxobacteria of the suborder Nannocystineae: An underexplored source of structurally intriguing and biologically active metabolites

Abstract: SummaryMyxobacteria are famous for their ability to produce most intriguing secondary metabolites. Till recently, only terrestrial myxobacteria were in the focus of research. In this review, however, we discuss marine-derived myxobacteria, which are particularly interesting due to their relatively recent discovery and due to the fact that their very existence was called into question. The to-date-explored members of these halophilic or halotolerant myxobacteria are all grouped into the suborder Nannocystineae.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 89 publications
(102 reference statements)
0
29
0
1
Order By: Relevance
“…have been found in marine environments and saline soils, and in the specific case of M . xanthus , it has been shown that cells can proliferate under osmotic stress 62 . Such a salt-tolerance can ensure M .…”
Section: Methodsmentioning
confidence: 99%
“…have been found in marine environments and saline soils, and in the specific case of M . xanthus , it has been shown that cells can proliferate under osmotic stress 62 . Such a salt-tolerance can ensure M .…”
Section: Methodsmentioning
confidence: 99%
“…In addition corallopyronin A was also tested successfully using an in vivo mouse model for the treatment of infections with filarial nematodes [ 44 ]. Such antibiotics produced by heterotroph bacteria, e.g., marine and terrestrial myxobacteria which can feed on other bacteria, are suggested as predatory weapons to paralyze and kill their prey [ 45 46 ].…”
Section: Reviewmentioning
confidence: 99%
“…The resulting intermediate I undergoes repeated 1,3-hydride shift/cyclization and the oxidation of the terminal methyl group. In silico analysis was carried out on the genome sequences of Enhygromyxa salina DSM 15201 (= E. salina SHK-1 T in Figure 2) [4] by antiSMASH (ver. 4.0.0) software (), revealing the presence of seven terpenoid biosynthetic gene clusters, three of which were found to contain a core gene homologous to a terpene (pentalenene) synthase gene.…”
Section: Resultsmentioning
confidence: 99%